Analysis of influencing factors of arterial calcification in non-dialysis patients with chronic kidney disease - CHEN Cai-ming; WU Meng; ZHANG Xiao-hong; WAN Jian-xin (Linchuang shenzangbing zazhi)
Objective To analyze the influencing factors of arterial calcification in non-dialysis patients with chronic kidney disease(CKD).Methods The 337 non-dialysis patients with CKD were enrolled.The clinical data were collected,including age,gender,body mass index(BMI),serum hemoglobin(Hb),albumin(Alb),blood alkaline phosphatase(ALP),blood urea nitrogenC BUN),serum creatinine(SCr),uric acid(UA),fasting blood glucose(FBG),total cholesterol(TCH),low density lipoprotein cholesterol(LDL-C),triglyceride(TG),high density lipoprotein cholesterol(HDL-C),serum calcium(Ca),serum phosphorus(P),serum magnesium(Mg),serum cystatin C,estimated glomerular filtration rate(eGFR),intact parathyroid hormone(iPTH),24-h urine protein excretion,C reactive protein(CRP),25 hydroxy vitamin D3,N-osteocalcin(NOC),and bone mineral density(BMD) of lumbar spine and femoral neck.The patients were divided into arterial calcification(including aortic calcification or coronary artery calcification) group and no arterial calcification group according to the spiral CT of chest.Results According to the spiral CT of chest,68 patients had aortic calcification and coronary artery calcification(20.2%),119 patients were had aortic calcification or coronary artery calcification(35.3%),and 150 patients had no arterial calcification(44.5%).The patients in arterial calcification group was older,hypertension and chronic nephritis were more commonly seen,serum higher triglycerides(TG),Cystatin C and CRP levels were higher,and eGFR was lower than in no arterial calcification group(all P<0.05).Spearman linear analysis revealed that there was a positive correlation between arterial calcification with LDL-C,BUN,SCr,Cystatin C,UA and iPTH,while a negative correlation between arterial calcification with Alb and eGFR Logistic regression analysis demonstrated that the protective factors of the aortic calcification were eGFR and hemoglobin,and no risk factors were found.Conclusions The patients with non-dialysis CKD have a higher incidence of arterial calcification.The eGFR and hemoglobin were the influencing factors of the arterial calcification in non-dialysis CKD patients.